-Parametric Bleimann Butzer and Hahn Operators - Mahmudov NI; Sabancıgil P (Journal of Inequalities and Applications, 2008)
Abstract We introduce a new -parametric generalization of Bleimann, Butzer, and Hahn operators in . We study some properties of -BBH operators and establish the rate of convergence for -BBH operators. We discuss Voronovskaja-type theorem and saturation of convergence for -BBH operators for arbitrary fixed . We give explicit formulas of Voronovskaja-type for the -BBH operators for . Also, we study convergence of the derivative of -BBH operators.